The “European Refugee Crisis” as the Crisis of Liberal Tolerance: Three Modalities of Liberal Exclusion - Hande Sözer (Alternatif Politika)
This article examines European residential responses to migrations after 2015. The literature meticulously analyzes their historically-contextually changing variances and inner diversities while imposing a binary view: the anti-immigration response is the negation, and the solidarity response is the affirmation of liberal tolerance. Contrarily, I argue that both responses utilize the liberal tolerance idea and its operational principles. First, they border the European Self and the migrant Other; re-border “the intolerable” and “the tolerable” migrant; and then exclude the former while only partially including the latter. Refugees’ inclusion and exclusion are seen either as a zero-sum (i.e., they are either included or excluded) or a dialectical state (i.e., the inclusion of some means the exclusion of others), but I claim that even the most inclusive responses are excluding the very subjects they claim to include. Inclusion is partial, while exclusion is constant. Thus, I discuss the migrants’ permanent yet differential exclusions in three modalities of liberal tolerance: Liberal intolerance, differentiating tolerance, and indifferent tolerance.